2009
DOI: 10.1051/forest/2009018
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality in a mixed deciduous forest in Northwestern Russia over 22 years

Abstract: Abstract• We studied mortality rates of birch, small-leaved linden, pedunculate oak, Norway maple, black alder, common ash and Norway spruce, assessed through two inventories of 12 664 trees in the unmanaged mixed deciduous forests of Oranienbaum Park, northwestern Russia, in 1981 and2003. • Our objectives were to evaluate if (a) long-term mortality rates vary among species, and if (b) crown condition, age and tree size affect the probability of mortality.• Over this period, tree mortality rates in the park va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Drobyshev et al (2008) suggests that for oak, density-regulated allogenic mortality may be of higher importance than exogenous mortality, especially in the beginning of its lifespan. Drobyshev et al (2009) found a significant and consistent association between tree condition and the probability of mortality, and significantly higher mortality rates in smaller trees of oak. The same variables as those finally included in the mortality model for Quercus pyrenaica have also been identified for others species: inverse of diameter at breast height (Bravo-Oviedo et al, 2006;Jutras et al, 2003;Karlsson and Norell, 2005); and individual height-dominant height ratio (Avila and Burkhart, 1992).…”
Section: Discussionmentioning
confidence: 61%
“…Drobyshev et al (2008) suggests that for oak, density-regulated allogenic mortality may be of higher importance than exogenous mortality, especially in the beginning of its lifespan. Drobyshev et al (2009) found a significant and consistent association between tree condition and the probability of mortality, and significantly higher mortality rates in smaller trees of oak. The same variables as those finally included in the mortality model for Quercus pyrenaica have also been identified for others species: inverse of diameter at breast height (Bravo-Oviedo et al, 2006;Jutras et al, 2003;Karlsson and Norell, 2005); and individual height-dominant height ratio (Avila and Burkhart, 1992).…”
Section: Discussionmentioning
confidence: 61%
“…In recent decades, inventories and dendroecological studies, combined with accurate historical climatic records, were significant sources of data for calibrating models of tree mortality (Bigler et al. 2007; Wunder 2007; Drobyshev, Dobrovolsky & Neshataev 2009). However, most studies were performed in ecotones, where signs of climate impact on forest ecosystems may be expected (Allen & Breshears 1998) and comparative assessments of climatic effects across dominant tree species or biome distributions are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is very interesting to determine the origin and period of existence of the lime-tree forest in the Lisino forest district. Analysis of mortality rates of the lime trees in the North-West (Eaton, Caudullo & de Rigo, 2016), as well as results of subsequent models of dynamics of the lime-tree forests (Drobyshev et al, 2009) evidence that the lime-tree woodlands can exist without reproduction during 400 years as a minimum. In accordance with the data provided by C.D.…”
Section: Resultsmentioning
confidence: 99%